Sustentabilidade das propriedades rurais do açude da Marcela em Itabaiana-Sergipe - Oliveira, Maria Gabriela Santos (2017)
The agricultural practice is an activity of great relevance for the maintenance of the life of the human beings and generation of jobs in the rural zone. However, in order for this practice to be sustainable, care must be taken with the environment where it is inserted, because the inappropriate handling of this activity can cause irreversible damage to the environment, besides making economic activity unfeasible and generating social conflicts. The Marcela reservoir, a research area, is a key factor in Sergipe's agricultural production. However, the dam region presents strong anthropogenic impacts resulting from the agricultural activities carried out in the surroundings, industrial activities, population growth in the region and domestic effluents released in the untreated reservoir of the city of Itabaiana. Considering the importance of agricultural practices and the impacts found in the region, the objective of this study was to evaluate the sustainability of the rural properties present in the Marcela reservoir region in Itabaiana-SE, through the tool of environmental sustainability analysis that involves the selection and measurement Of indicators, known as MESMIS "Framework for Evaluation of Natural Resource Management Systems Incorporating Sustainability Indicators". The results indicated that the three dimensions studied presented inferior indexes of ideal quality of sustainability, thus showing weaknesses in the system, and for these to be remedied, it is essential that the recommendations proposed by this research be supported and adopted, as well as basic activities Management and continuous analysis of sustainability in the social and economic environment.